Control of Layering in Aurivillius Phase Nanocomposite Thin Films and Influence on Ferromagnetism and Optical Absorption - Mühlenbein L.; Singh C.B.; Singh A.K.; Fina I.; Himcinschi C.; Lotnyk A.; Bhatnagar A. (My University, 2025)
Layered structures in complex oxide systems, reminiscent of superlattices, albeit naturally occurring, are often considered superior than their respective rudimentary forms. The enhanced functionalities related to the ferroic character have been known for a while now, and the enhanced photoelectrical properties have been only very recently demonstrated. Despite the improved performance, synthesis of such structures with precise control remains to be a bottleneck. In this work, this issue is addressed with a perovskite phase target of (PbTiO3)0.65(BiNi2/3Nb1/3O3)0.35. The deposition parameters are shown to have a deterministic control over the phase of the resultant thin film, that is, a layered Aurivillius phase or a perovskite phase. The resultant layered phase is demonstrated to have superior ferroic properties, in addition to an improved light absorption in the visible regime, thus making it an attractive photoferroic system. © 2022 American Chemical Society.